Legal regulation of the police officers' powers of the Ukrainian SSR in the 1920s of the XX century (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The scientific study is devoted to the peculiarities of the legal regulation of the police officers’ powers of the Ukrainian SSR in the 20s of the XX century. The problems of the activities of the police of the Ukrainian SSR in the period under study were studied by V. Hrechenko, O. Bandurka, O. Yarmysh, I. Kotsan and other researchers. The norms of the legislative and by-laws of the USSR, which established the rights and duties of police officers, have been analysed. The departmental and local by-laws norms of various authorities of the Ukrainian SSR, which set additional tasks for police officers, have been studied. The documents containing information on the functions and tasks of police officers in certain settlements of the Ukrainian SSR during the period under study have been studied.The legislative acts of the USSR, on which the Soviet police was based, also determined the powers of the employees of this authorityIn the early 20s of the XX century, the powers of police officers were enshrined in the Regulation on the Workers’ and Peasants’ Police of the Ukrainian SSR dated September 14, 1920. In the second half of the 1920s the rights and duties of police officers were established in the Regulations on the Workers’ and Peasants’ Militia dated November 10, 1926, and the Administrative Code of the Ukrainian SSR dated 1927. Police officers had to fulfill their duties to protect the revolutionary order and public safety. The Administrative Code of the Ukrainian SSR established the powers of police officers to carry out searches and seizures, requisitions and confiscations, the use of weapons, citizen detention, and the imposition of administrative fines. The powers of police officers in the field of the preliminary investigation were established in the Criminal Procedure Codes of the USSR dated 1922 and 1927.It has been concluded that in the first half of the 1920s of the XX century, police officers were often involved in performing tasks that were not typical of law enforcement activities. At the same time, in the second half of the 1920s, legislative and by-law acts were adopted on the police officer exemption from performing tasks that were not typical for them.
Keywords: police officers; powers; rights and duties; legal regulation.